HYPERTONIC SOLUTIONS EFFICACY IN ACUTE UNCOMPLICATED RHINOSINUSITIS TREATMENT IN CHILDREN - М.R. Bogomilskiy; E.Yu. Radzig; D.V. Shklyar (Вопросы современной педиатрии, 2011)
The article is dedicated to the problem of acute rhinosinusitis in children. It contains data from our own research upon hypertonic solution efficacy and suitability in complex therapy of rhinosinusitis. It was shown that inclusion of hypertonic solution of sea water spray into treatment scheme of acute rhinosinusitis allows to reach amelioration of nasal functions and patient’s well being in short term, reduces total duration of the disease, thus decresing the risk of complications development. Key words: rhinosinusitis, treatment, childhood, hypertonic solution, sea water. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (5): 124–129.)